Signal Penetration towards Wooden Building Construction Materials - Kho, L.C.; Ngu, S.S.; A., Baharun; Lias, K. (IEEE, 2007)
This paper emphasize on the effect of mobile signal penetration towards wooden building construction materials in Malaysia. The results of signal strength measurement at frequency 900MHz in the anechoic chamber with different types of wooden building construction materials and thickness is presented. The objectives of these experiments are to identify the types of wooden building materials in Malaysia that have significant impact into signal penetration and determine the effect of the identified wooden materials thickness towards signal penetration into building materials. This paper also report on the anechoic chamber and experiment setup that is used in the experiment